2018
DOI: 10.3389/fcimb.2018.00319
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gut Microbiota Prior to Influenza A Virus Infection Do Not Affect Immune Responses in Pups or Juvenile Mice

Abstract: Previous studies demonstrated that oral antibiotic (ABX) treatment prior to and during influenza A virus (IAV) infection of adult mice profoundly altered gut microbiota (GM) and was associated with increased susceptibility and impaired immunity to IAV. We examined the impact of ABX during critical times relevant to the establishment of GM in early life (using perinatal treatment of neonates and direct treatment of juvenile mice) and asked whether cessation of ABX treatment in early life had lasting effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…In addition, interferon production in the lungs have also been reported to alter the composition of intestinal microbes (Wang et al, 2014 ; Deriu et al, 2016 ). Similar to previous studies (Fuglsang et al, 2018a , b ), we found that the abundance of A. muciniphila significantly increased after influenza infection. A recent literature has shown that influenza infection enhanced intestinal Muc2 levels (Deriu et al, 2016 ), which may be related to the upregulation of A. muciniphila , due to muc2 is an essential ingredient to maintain the growth of A. muciniphila .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, interferon production in the lungs have also been reported to alter the composition of intestinal microbes (Wang et al, 2014 ; Deriu et al, 2016 ). Similar to previous studies (Fuglsang et al, 2018a , b ), we found that the abundance of A. muciniphila significantly increased after influenza infection. A recent literature has shown that influenza infection enhanced intestinal Muc2 levels (Deriu et al, 2016 ), which may be related to the upregulation of A. muciniphila , due to muc2 is an essential ingredient to maintain the growth of A. muciniphila .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, reduced levels of virus‐specific T‐cells to influenza virus were reported by Abt and colleagues due to changes in macrophage function in antibiotic‐treated mice . Conversely, IAV infection has been reported to not be influenced by antibiotic treatment in immature mice . However, how antibiotic treatment influences pulmonary ILCs in pathogenic infections remains to be elucidated.…”
Section: Microbiota – Ilc Axis During Infectious Diseasesmentioning
confidence: 98%
“…133 Conversely, IAV infection has been reported to not be influenced by antibiotic treatment in immature mice. 134 However, how antibiotic treatment influences pulmonary ILCs in pathogenic infections remains to be elucidated.…”
Section: Microbiota and Ilcs In Viral Infectionsmentioning
confidence: 99%
“…Colonization of the gastrointestinal tract by microorganisms commences at birth, immediately after delivery, and the succession of new bacterial colonizers have been shown to be essential for development of the immune system [16][17][18]. Not surprisingly, reduced microbiota diversity as a result of ABX treatment or germfree conditions in early life can affect development of the immune system [19][20][21]. Making the host more vulnerable to infection.…”
Section: Introductionmentioning
confidence: 99%